Learners’ experiences of creative writing in English First Additional Language: Pedagogical implications - Nondabula, Nikiwe; Nomlomo, Vuyokazi (Journal for Language Teaching, 2023)
This paper is based on a qualitative study that investigated Grade 9 learners’ experiences of creative writing in English first additional language (FAL). Following a social constructivist approach to learning, the paper argues that creative writing is a complex process that demands cognitive and metacognitive skills, so that the language in which learners write matters, since it determines the quality and level of creativity that learners portray in their writing. The study was conducted in a township school in the Western Cape Province of South Africa, and its aim was to investigate Grade 9 learners’ experiences of creative writing in English FAL. Data was collected by means of focus group interviews with selected Grade 9 learners. The key findings of the study indicate that while the learners experienced language-related challenges, they also acknowledged the linguistic and cognitive benefits of creative writing in English. The study concludes that while learners portray positive attitudes towards English, this language remains a barrier to their learning, especially with regard to creative writing that demands imagination and critical thinking. This article recommends that creative writing be given more attention in schools, and that writing in the official languages be encouraged to enhance learners’ creativity and literacy development.